Water quality and the presence of antibiotic resistant bacteria in the bayous of southeastern Louisiana, USA - Biju, Bincy; Boophaty, Raj; Arceneaux, Emily; Ledet, Zachary (Environmental and Toxicology Management, 2025)
Antibiotic resistance has become a significant public health concern due to the improper consumption and disposal of antibiotics. Improper handling often leads to selective pressure among bacteria that can lead to antibiotic resistance. Terrebonne parish in Louisiana being heavily populated, is dependent on Bayou for its seafood, recreational activities, transportation, and source of living. The water quality of Bayou Terrebonne and Bayou Petite Calliou has never been monitored before. The purpose of this study was to monitor the water quality of Bayou Terrebonne and Bayou Petite Calliou. Four sites along the bayous were monitored for water chemistry, total and fecal coliforms, and antibiotic resistance. The water samples were collected in triplicate and checked for the presence of antibiotic-resistant bacteria, coliforms bacteria, and the levels of organic carbon, nitrogen, ammonia, sulfate, and phosphate. The antibiotics tested on samples includes Tetracycline, Penicillin, Amoxicillin, Sulfamethoxazole-Trimethoprim, Bacitracin, Streptomycin Meropenem, and Erythromycin. The results showed that the bayou meets the criteria set by the Louisiana Department of Environmental Quality (LDEQ) for water chemistry except for sulfate concentration. The amount of total and fecal coliform exceeded the water quality standard due to fecal contamination from the discharge of untreated and/or under treated domestic wastewater from failing septic tanks and individual household sewage treatment systems along the bayous. Many antibiotic resistant bacteria and resistance genes were isolated from the water samples. The water is heavily impaired by the fecal contamination and the antibiotic resistant bacteria due to improper disposal of individual sewage treatment plant from households along the bayous.